HUBUNGAN BEBERAPA FAKTOR DENGAN PRAKTIK HYGIENE GENITALIA EKSTERNAL PADA REMAJA PUTRI PONDOK PESANTREN AL-ISHLAH TEMBALANG SEMARANG TAHUN 2016 - Luthfi Adibah; Djoko Nugroho; Sri Winarni (Jurnal Kesehatan Masyarakat (Undip), 2016)
Some of adolescents research showed that they often be wrong in cleaning their genitals. Prevalence of infection due in Indonesia is 43/100 inhabitants and have ranks seventh leading cause of death (5,7%). The high prevalence of infection due to lack of the external genital hygiene practices. Based on the previous study from  20 female students, there were 11 female students among less knowledgeable about how to clean their external genitals. This study aimed to analyze some factors related to the practice of external genital hygiene in girls adolescent at Al Islah Boarding School Tembalang-Semarang.This research type was Explanatory Research with Cross Sectional Study design time. The population was 60 female students and the sample was 50 female students with the inclusion criteria . The results of univariate analysis showed that the highest percentage of respondents that good knowledge was (54%), mothers education with primary education was (62%), the role of unfavorable friends was (54%) and external genital hygiene practices less good was (56%). The bivariate analysis using Yates correction test showed that there was a relationship of knowledge (p value = 0.001> 0.05), mothers education (p value = 0.004 <0.05), the role of friend (pvalue = 0.002 <0.05) with the external genital hygiene practices. It suggested to BKKBN which cooperate with Bapermasper to increase the female students empathy by giving information on the external genital hygiene and the interpersonal communication regularly with the boarding school management.